Providing Nafkaḥ Muṭ‘ah for Wives in Lawsuits of Divorce According to Islamic Law and Indonesian Legislation - Triana, Titin; Suhar, Suhar; Ishaq, Ishaq (Journal of Comprehensive Islamic Studies, 2023)
This article discusses the phenomenon of responsibility in granting mut‘ah to a divorce suit filed by the wife, both from the perspective of Islamic law and the perspective of legislation in Indonesia. The main problem studied is how Islamic law and legislation in Indonesia regulate the granting of mut‘ah to a divorce suit filed by the wife? This article comes from qualitative literature research which observes the phenomenon of court decisions regarding responsibility for granting mut‘ah. The research found that based on the provisions of Chapter 149 of the Compilation of Islamic Law (KHI), in divorce cases that are contested in trials at the Religious Courts, the judge does not punish husbands who commit mut‘ah and undergo iddah. The obligation to provide mut‘ah and iddah is only given by husbands who divorce their wives as mandated in article 39 of PP No.9 of 1975 jo. Chapter 149 letter (b) Compilation of Islamic Law (KHI). Artikel ini membahas tentang fenomena tanggung jawab dalam pemberian mut‘ah kepada gugatan cerai yang diajukan oleh pihak istri, baik dari segi Hukum Islam dan maupun perspektif perundang-undangan di Indonesia. Permasalahan utama yang dikaji adalah bagaimana Hukum Islam dan Perundang-undangan di Indonesia mengatur tentang pemberian mut‘ah kepada gugatan cerai yang diajukan oleh pihak istri? Artikel ini berasal dari penelitian kualitatif literatur yang mengamati fenomena putusan pengadilan terkait tanggungjawab pemberian mut‘ah. Penelitian menemukan bahwa Berdasarkan ketentuan Bab 149 Kompilasi Hukum Islam (KHI),  dalam perkara perceraian yang digugat dalam persidangan di Pengadilan Agama, Hakim tidak menghukum suami yang melakukan mut‘ah dan menjalani iddah. Kewajiban memberikan mut‘ah dan iddah hanya diberikan oleh suami yang menceraikan istrinya sebagaimana diamanatkan dalam pasal 39 PP No.9 Tahun 1975 jo. Bab 149 huruf (b) Kompilasi Hukum Islam (KHI).